HARDINESS IN THE STRUCTURE OF PERSONAL RESOURCES CONDUCIVE TO OVERCOMING PROFESSIONAL BURNOUT AMONG WORKERS DURING A PANDEMIC - I. Rerke, Viktoriya; V. Belyakova, Natalia; B. Mottaeva, Angela; P. Shipovskaya, Lyudmila; V. Ignatyeva, Alla; V. Blinov, Leonid; G. Kalina, Irina (Revista Gênero e Interdisciplinaridade, 2021)
Today, the risk of emotional exhaustion is increasing and a decrease in the professional activity of healthcare workers is observed due to an epidemiologically unstable situation in the world. The importance and social significance of solving this problem is connected with the fact that the burnout syndrome has a complex form and can be interpreted differently from the point of view of root causes and final outcome. This, in its turn, guides to the exploratory search for directions of psychological means and methods of influence. The purpose of the paper is to study hardiness in the structure of personal resources of overcoming professional burnout among healthcare workers during a pandemic. The leading techniques for the study of this problem were the following: psychodiagnostic technique “Diagnosis of emotional burnout”, personality questionnaire, hardiness test. Hardiness has been studied in the structure of personal resources of overcoming professional burnout. The authors have proven that doctors possessing hardiness are distinguished by personal qualities that help them adapt and withstand difficult social situations. The features of professional burnout have been identified among healthcare workers during the Covid-19 pandemic. It has been found that a high level of hardiness in the structure of personal resources is a factor in overcoming professional burnout among doctors. The results obtained made it possible to develop practical recommendations to prevent professional burnout and boost hardiness among healthcare workers during the pandemic. The paper is intended for specialist psychologists, clinical psychologists, and healthcare managers.